Reação de genótipos de soja ao mofo branco - Andrade, Gabriela Carolina Guimarães (2015)
White Mold, caused by Sclerotinia sclerotiorum fungi, is, currently, one of the most important diseases of soybean, causing considerable economic losses and is of difficult control. The Fungi has more than 400 host species, including crops of agronomical importance as soybean, common beans and sunflower. The dissemination is mainly accomplished by infected seeds or by the presence of sclerotium. Genetic resistance is the most effective of plant disease control but is not well known about the soybean varieties resistance in Brazil and the current inoculation methods do not always have good correlation with field data. The main goals of this study were the evaluation of the resistance of soybean genotypes in two environments, Barreira – BA and Jatai – GO, correlate the rainfall with the variables analyzed, test two different methods, one in the greenhouse using tooth pick and other in the laboratory using oxalic acid, as well as correlate the data from the experiments in the fields with the greenhouse and the sensibility to the oxalic acid. According to the data analyzed, there are differences between genotypes of soybean in respect to the resistance of white mold. Early genotypes and more resistant to lodging were more resistant to white mold, but showing variations in the results. There was interaction between environment and soybean genotypes. The environment influenced meaningfully the occurrence of the disease in the tested genotypes, where in the severity correlate negatively and meaningfully with yield, in other words, the bigger the severity, the less the yield. The genotypes ANTA82, 2011L003 and 2011L005 had higher yields and were genetically more resistant to the disease. In respect to the methods used for the selection of resistant genotypes to white mold, it was seen that the oxalic acid method is an alternative for selection of resistant genotypes, since the variability of the pathogen is not considered, using the physiological traits of the genotypes. The experiments in the greenhouse are not correlated to the experiments in the field, due to the difficulty of reproducing equal symptoms that normally occur in the field. However, the method of the oxalic acid was shown to be reliable to be used in the phenotype of soybean cultivars but methodology adjusts should be done in future tests.